Acceptance of independent curriculum in North Kalimantan - Setyaningsih, Agustina; Bagea, Ishak; Mulyadi, Mulyadi; Sarip, Mohamad; Agustiwi, Asri; Mubarok, Ence Supriatna; Haetami, Aceng (Journal of Education and Learning (EduLearn), 2024)
Determining the curriculum is the government's authority, in early 2022, the independent curriculum was launched. Implementing an independent curriculum is a challenge in itself for education in North Kalimantan. The reason is educational facilities in this region are not evenly distributed. However, several agencies have made efforts to continue to make the independent curriculum program a success. This research was conducted using the systematic literature review (SLR) method. The results of this research are that the government, teacher groups, and several schools have developed and implemented an independent curriculum. Teaching staff in North Kalimantan experienced various difficulties in implementing the independent curriculum technique, including a lack of resources, such as teaching materials and technology, and confusion due to a lack of understanding. This case is an indication that there is still a need to improve the quality of education, especially in the interior of North Kalimantan.